Clonagem e modelagem molecular de duas lectinas tipo C (LvCTL-br1 e LvCTL-br2) de Litopenaeus vannamei - Costa, Francisco Hiran Farias (2009)
C-type lectins are animal proteins of about 130 amino acids long, containing at least one carbohydrate recognition domain (CRD) capable of mediating sugar and calcium binding. The carbohydrate recognition is directly related to some biological activities, like cell-cell adhesion, serum glycoprotein turnover, and innate immune responses against potential pathogens. In invertebrates, like insects and crustaceans, C-type lectins act as pattern recognition receptors (PRRs), by binding to pathogen associated molecular patterns (PAMPs) and activating the innate host defense systems. In addition to their function as PRRs, it has been shown that in economically important penaeid shrimp species, C-type lectins function as antimicrobial and antiviral protein, component of pathogen clearence and innate immune response. The penaeid shrimp C-type lectins fall into two structurally classes of related proteins, based on the presence of a single CRD per molecule of protein or two juxtaposed CRDs with a spacer sequence in between. It has known that a given lectin activity depends not only of the presence of CRDs and other conjugated domains, but also of its global architecture. So far, for structural studies, we have cloned two novel c-type lectins from the hepatopancreas of juvenile Litopeneaus vannamei. The cloned cDNAs encompass ORFs of 1044 nt and encode high similar (99.6%) two-domains proteins of 347 residues. Named Lv CTL-br1 and LvCTL-br2, their estimated molecular masses and values of pI are 38.4 kDa and 4.93 (LvCTL-br1), and 38.5 kDa and 4.87 (LvCTL-br2). In both proteins the consensus triad that recognizes galactose (-QPD-), in CRD-1 is preserved, but the mannose-binding site (-EPN-), in the second domain, was mutated. Computational molecular modeling of LvCTL-br1 and LvCTL-br2 reveals domain structures constituted by a-helix chain interlaced by loops and a single 3-sheet. In contrast to CRD-1 of Lv CTL-br1, the CRD-2 presents a long loop that might accommodate complex sugars. The 3-D models also show that three amino acid substitutions, in CRD-1, occur close to the sugar binding site. Interestingly, a nonsynonymous substitution of GIy109 for Asp109, observed in CRD1 of LvCTL-br2, indicates that three hydrogen bounds might be formed between complex carbohydrates, what could reflect in a higher affinity by the sugar. The present work is the first to present the cloning of two L. vannamei hepatopancreatic C-type lectins with mutated mannose binding site, and their respective molecular 3-D models.